Comparison of Bacterial Expression Systems Based on Potato Virus Y-like Particles for Vaccine Generation - Ogrina, Anete; Skrastina, Dace; Balke, Ina; Kalnciema, Ieva; Jansons, Juris; Bachmann, Martin F.; Zeltins, Andris (Vaccines (Basel), 2022)
Plant-based virus-like particle (VLP) vaccines have been studied for years, demonstrating their potential as antigen-presenting platforms. In this paper, we describe the development of, and compare between, simple Escherichia coli-based antigen display platforms for the generation of potato virus Y (PVY) VLP-derived vaccines, thus allowing the production of vaccines from a single bacterial cell culture. We constructed four systems with the major cat allergen Fel d 1; namely, direct fusion with plant virus PVY coat protein (CP), mosaic PVY VLPs, and two coexpression variants of conjugates (SpyTag/SpyCatcher) allowing coexpression and conjugation directly in E. coli cells. For control experiments, we included PVY VLPs chemically coupled with Fel d 1. All constructed PVY–Fel d 1 variants were well expressed and soluble, formed PVY-like filamentous particles, and were recognized by monoclonal Fel d 1 antibodies. Our results indicate that all vaccine variants induced high titers of anti-Fel d 1 antibodies in murine models. Mice that were immunized with the chemically coupled Fel d 1 antigen exhibited the highest antibody titers and antibody–antigen interaction specificity, as detected by binding avidity and recognition of native Fel d 1. IgG1 subclass antibodies were found to be the dominant IgG class against PVY–Fel d 1. PVY CP-derived VLPs represent an efficient platform for the comparison of various antigen presentation systems to help evaluate different vaccine designs.